Making index-based flood insurance socially inclusive in Bangladesh: challenges and options - Aheeyar, Mohamed M. M.; de Silva, Sanjiv; Senaratna Sellamuttu, Sonali (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Floods and other weather-related disasters plague farmers in Bangladesh, and climate change threatens to exacerbate these risks. At stake are the livelihoods of millions of small and marginal farmer households that are at risk of becoming further entrenched in poverty. Lack of compensation or other buffering mechanisms means crop losses give rise to deepening cycles of debt, especially when cultivation is financed through loans. While neighboring India has developed strong policy and strategic direction for using risk transfer mechanisms, such as Weather Index Insurance (WII), as a disaster risk reduction tool, policy support in Bangladesh is lukewarm. To date, most WII schemes have been pilots implemented mainly by nongovernmental organizations (NGOs) and donors. The Index-based Flood Insurance (IBFI) project of the International Water Management Institute (IWMI) hopes to adapt the pilot scheme it is trialling in Bihar, India, to Bangladesh. To understand how such a scheme can be made accessible, especially to marginal groups, fieldwork was undertaken in Sirajganj district. Here, a WII pilot project, funded by the Asian Development Bank (ADB), which offers insurance for crops during both the Aman and Boro seasons is ongoing. This brief is informed by findings from this fieldwork.